Clinical Usefulness of Sensitivity Prediction by Acoustic Reflex (SPAR) in Evaluating Hearing in Children - Joan D'Mello (Journal of All India Institute of Speech and Hearing, 1970)
Assessment of hearing In children is more interesting and meaningful today The arrival of immittance testing and brainstem evoked response audiometry (BERA) has revolutionized the previously less exciting measurement of hearing in children. One such revolution is prediction of hearing loss using acoustic reflex. Prediction of hearing loss using acoustic reflex is based on the concept of noise-tone difference, i.e., the acoustic reflex is elicited at low intensity levels by noise than tone.This difference is reduced in subjects with sensorineural hearing loss. Based on this concept several prediction methods have come into existence. And sensitivity prediction using Acoustic Reflex (SPAR) is one of them (Jerger et  al, 1974).